Non-medical use of prescription drugs and cultural orientation among college students in China. (1st November 2018) - Tam, Cheuk Chi; Benotsch, Eric G.; Wang, Xiaolei; Lin, Danhua; Du, Hongfei; Chi, Peilian
Highlights: Chinese college students reported high rates of nonmedical use of prescription drugs. Analgesics were the class of medication most commonly used nonmedically. Individualism was associated with nonmedical use of prescription drugs. Abstract: Background: Due to a dramatic increase in the past 20 years, the non-medical use of prescription drugs (NMUPD) has become a global public health issue. College students have high prevalence of NMUPD in the United States. However, limited studies have been conducted among Chinese students. The purposes of this study were to examine the prevalence of NMUPD among college students in two urban centers (Beijing and Macau) in China and assess its relationships with cultural orientation (collectivism - primary focus on the group and individualism - primary focus on the individual). Methods: In January–April 2017, 849 undergraduates (72.2% female) from Beijing and Macau, with an average age of 20 completed online surveys about their demographics, NMUPD, and cultural orientation. Results: Overall, 62.9% (lifetime) and 33.4% (past three-months) of students in Beijing reported NMUPD, while 35.9% (lifetime) and 21.8% (past three-months) of students in Macau reported NMUPD. The most commonly non-medically used class of medicine (lifetime) was analgesics (62.9% Beijing; 35.5% Macau), followed by sedatives (4.0% Beijing; 0.9% Macau), anxiolytics (2.7% Beijing; 0.6% Macau), and stimulants (1.0% Beijing; 0.2% Macau). Multivariate analyses suggested a positive association of individualism with lifetime NMUPD (OR = 1.78, 95% CI = 1.15, 2.75, p < .01 in Beijing; OR = 1.53, 95% CI = 1.16, 2.02, p < .01 in Macau). Conclusion: NMUPD in Chinese college students appears to be common. More discussion is needed in China about regulation of prescription drugs. Future culturally-tailored NMUPD-risk reduction intervention programs may be beneficial to Chinese college students.